Correlations between cardiovascular parameters and image parameters on dynamic chest radiographs in a porcine model under fluid loading - Tanaka, Rie; Tani, Tohru; Yamada, Atsushi; Tani, Soichiro; Dang, Khiem Tran; Nitta, Norihisa; Tabata, Takahisa; Muraoka, Shintaro; Yoneyama, Tsutomu; Sanada, Shigeru (Radiological physics and technology, 2021)
Latest digital radiographic technology permits dynamic chest radiography during the cardiac beating and/or respiration, which allows for real-time observation of the lungs. This study aimed to assess the capacity of dynamic flat-panel detector (FPD) imaging without the use of contrast media to estimate cardiovascular parameters based on image parameters of a porcine model under fluid loading. Three domestic pigs were intubated, and mechanical ventilation was provided using a ventilator under anesthesia. A porcine model involving circulatory changes induced by fluid loading (fluid infusion/blood removal) was developed. Sequential chest radiographs of the pigs were obtained using a dynamic FPD system within the first 5 min after fluid loading. Image parameters such as the size of the heart shadow and mean pixel values in the lungs were measured, and correlations between fluid loading and cardiovascular parameters (blood pressure [BP], cardiac output [CO], central venous pressure [CVP], and pulmonary arterial pressure [PAP]) were analyzed based on freedom-adjusted coefficients of determination ( R f 2 ). Fluid loading was correlated with radiographic lung density and the size of the heart shadow. Radiographic lung density was correlated with the left and right heart system-related parameters BP, CO, CVP, and PAP. The size of the heart shadow correlated with the left heart system-related parameters CO and BP. Dynamic FPD imaging allows for the relative evaluation of cardiovascular parameters based on image parameters. This diagnostic method provides radiographic image information and estimates relative circulatory parameters.